Neutron Flux Variation at the Inner Irradiation Channel of the Nigeria Research Reactor-1 (NIRR-1) - Musa, Y.; Ahmed, Y.A.; Yamusa, Y.A.; Tukur, M. (Journal of Technology Innovations in Renewable Energy, 2014)
In order to ascertain the level of flux variation in one of the inner irradiation channels of the Nigeria Research Reactor-1 (NIRR-1), the irradiation container used for routine activation analysis was employed with copper wires as flux monitors. Measurements were carried out with these wires arranged in axial direction to determine the thermal neutron flux at selected positions using absolute foil activation method. Our results show that there exists a slight flux variation from one position to another ranging from (4.57 ± 0.24) x 1011 to (5.20 ± 0.20) x 1011 cm-2s-1. Individual foil shows slight flux variation from one position to another in the same irradiation container but they all pointed toward a level of stability in spite of the recent installation of the cadmium lined irradiation channel. The values obtained in this work are in good agreement with the previously measured value of (5.14 ± 0.24) x 1011 cm-2s-1 after commissioning of NIRR-1. This shows that the cadmium lined installation does not affect the flux stability. In order to improve the accuracy of neutron activation analysis (NAA) using NIRR-1 facility, there is need for flux corrections to be made by miniature neutron source reactor (MNSR) users during NAA particularly long irradiation, where more than six samples are irradiated simultaneously in the same container.